Post Covid-19 impact of Availability Bias Effect on Investment Decisions of Pakistan Stock Exchange Registered Brokers Investors - Rahim, A.; Khan, Faisal; Mehmood, S.; Muhammad, L. (2022)
In this study researcher analyzed Post Covid-19 impact of Availability effect bias on investment decisions of Pakistan Stock Exchange (PSX) after pandemic. Financial markets post Covid-19 changed the dynamics all over the World and affected investment decisions of investors of Broker houses registered with PSX. Conventional investments like maintaining saving bank account or booking of Fix term deposit, investments in mutual funds, buying Prize bonds or gold bars are outmoded investments Post Covid-19. Investor now evaluate thousands of options including e-currency investments and invest more wisely than before Covid19. They try to capitalize the opportunity of higher returns now in one of the volatile stock market PSX which is again gaining momentum after change in Government from PTI to PML-N recently in last week of ramzan-2022. Pakistani stock market is one of those volatile market where not only local but foreign investors are investing and buying shares through registered Brokers of PSX has raised and drop the KSE-100 index from 1st Jan to 4th May-2022 many times due to Availability effect bias. Researchers made an attempt to address post Covid-19 influence of Availability effect bias on investment decisions of PSX investors registered with Broker by taking Availability effect bias along with its sub variables as an independent variable and investment decision of these investors as dependent variable and evaluated the impact of both variables in post Covid-19 Pakistani stock market performance. Researcher used stratified random sampling technique by dividing Pakistani stock market such as: Karachi Stock exchange (KSE), Lahore Stock Exchange (LSE) and Islamabad Stock Exchange (ISE). The study is quantitative in nature, so questionnaire survey technique was employed for data collection from registered PSX brokers investors of KSE, LSE and ISE. Theory of mental accounting of behaviors finance is backing this study and has served the base for this study. Researcher used descriptive statistics, rank correlation and its analysis, association method and applied logistic regression model. Findings of this study suggest that Post Covid-19 impact of Availability effect bias on investment decisions of PSX have positive impact on individual investors decisions at Pakistani stock market.